Effect of carbonaceous oil palm leaf quantum dot dispersion in nematic liquid crystal on zeta potential, optical texture and dielectric properties - Rastogi A.; Pandey F.P.; Parmar A.S.; Singh S.; Hegde G.; Manohar R. (My University, 2025)
In the present work, the dispersion of oil palm leaf based carbonaceous quantum dots (OPL QDs) in nematic liquid crystal (NLC) E 48 eutectic mixture has been reported. The dispersed systems with concentrations 0.1, 0.2, and 0.3 wt% are designated respectively, as MIX 1, MIX 2, and MIX 3. The objective of this study is to analyze the results on the zeta potential, optical texture, dielectric constant, dielectric loss, conductivity, dielectric strength, relaxation frequency, specific power loss and total power loss of pure and OPL QDs dispersed nematic E 48 system. Zeta potential measurement has been performed in the solution state to ensure dispersion stability. The optical textures and dielectric results are recorded after filling the respective samples in sample cells. The core findings in the present study show that the zeta potential varies from − 23.43 mV to + 28.07 mV that signifies the stability of OPL QDs suspension in LCs. Specific power loss (SPL) and total power loss (TPL) are found to be least for MIX 1 which shows that the problem of high power consumption in LCDs can be resolved by dispersing a small weight percent concentration of OPL QDs in LC medium (MIX 1). Improved molecular alignment in the dispersed system has been observed from the textural study which finds its application in good contrast display devices. The color change in the aligned textures with temperature has been attributed to the birefringence change. The porous nature of carbonaceous OPL QDs has its application in supercapacitors. The benchmark results of this study highlight the effect of temperature and frequency on dielectric parameters for both planar and homeotropic state of E 48 LCs. OPL QDs dispersed system display increased conductivity for MIX 3. The decrease in the activation energy for OPL QDs dispersed system in comparison to pure LC material E 48 is a consequential result of the potential barrier change. The increment in the dielectric strength and relaxation frequency of OPL QDs dispersed system is noticed in comparison to pure E 48. These outcomes open the door for the applicability of present LCs in the field of both display and non-display devices like sensors, supercapacitors, low power consumption displays, energy conversion, and electrical storage devices as well as advanced smart systems. Graphical abstract: [Figure not available: see fulltext.]. © 2021, Islamic Azad University.